Double-lumen tubes and auto-PEEP during one-lung ventilation. (January 2016) - Spaeth, J.; Ott, M.; Karzai, W.; Grimm, A.; Wirth, S.; Schumann, S.; Loop, T.
Abstract: Background: Double-lumen tubes (DLT) are routinely used to enable one-lung-ventilation (OLV) during thoracic anaesthesia. The flow-dependent resistance of the DLT's bronchial limb may be high as a result of its narrow inner diameter and length, and thus potentially contribute to an unintended increase in positive end-expiratory pressure (auto-PEEP). We therefore studied the impact of adult sized DLTs on the dynamic auto-PEEP during OLV. Methods: In this prospective clinical study, dynamic auto-PEEP was determined in 72 patients undergoing thoracic surgery, with right- and left-sided DLTs of various sizes. During OLV, air trapping was provoked by increasing inspiration to expiration ratio from 1:2 to 2:1 (five steps). Based on measured flow rate, airway pressure ( P aw ) and bronchial pressure ( P bronch ), the pressure gradient across the DLT (Δ P DLT ) and the total auto-PEEP in the respiratory system (i.e. the lungs, the DLT and the ventilator circuit) were determined. Subsequently the DLT's share in total auto-PEEP was calculated. Results: Δ P DLT was 2.3 (0.7) cm H2 O over the entire breathing cycle. At the shortest expiratory time the mean total auto-PEEP was 2.9 (1.5) cm H2 O (range 0–5.9 cm H2 O). The DLT caused 27 to 31% of the total auto-PEEP. Size and side of the DLT's bronchial limb did not impact auto-PEEP significantly. Conclusions: Although the DLT contributes to the overall auto-PEEP, its contribution is small and independent of size and side of the DLT's bronchial limb. The choice of DLT does not influence the risk of auto-PEEP during OLV to a clinically relevant extent. Clinical trial registration: DRKS00005648.